A relação entre teoria e prática e a formação do professor de língua estrangeira (inglês) : processos identitários - Araújo, Nélio Martins (2006)
This dissertation aims at analyzing, discursively, open reports of English teachers with or without academic training in the field of teaching and learning foreign languages at private language schools. We have tried to identify how teachers conceive the role of theory as well as their theoretical and practical training in their pedagogical performance. Theoretically, this research was carried out by following the concepts of the French School of Discourse Analysis. The study assumed the hypothesis under which there are differences among teachers who have had academic training and those who have not, although these have been trained through different kinds of contacts with theory. Thus, utterances of English teachers were analyzed and we were able to realize, on the on hand, the presence of an imaginary of absence and ignorance of theory in the reports of those without academic training and an imaginary of presence and validation of those with academic training. It was also identified that theories from Applied Linguistics crossed the discourse of teachers about theory and practice, which was explained by the very fact that Applied Linguistics is present in the curriculum of teacher training courses at the university. Results have shown that the relation between theory and practice tends to be dichotomic. It privileges theory in detriment to practice. After the data analysis, we verified that the relation between theory and practice should be seen under a view of relay among them and not as a view of totalization. Admitting that the teachers pass through moments of identification in their constitution process as teachers, and these moments will join to other identification moments that occur in their pedagogic performance spaces, we have verified that the tensions are established and, by this, they mark the teachers identity constitutions.